2009
DOI: 10.1042/cs20080413
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in serum oxidant/antioxidant status in overfed obese rats and their offspring

Abstract: The aim of the present study was to determine the time course of changes in oxidant/antioxidant status, as well as serum glucose, insulin, leptin and lipid levels, liver adipose tissue and muscle lipid and protein contents, in cafeteria-diet-fed dams during gestation and lactation, and in their offspring throughout adulthood. Food intake was also evaluated. The cafeteria diet induced a significant increase in maternal body and relative adipose tissue weights, daily energy intake, and plasma glucose, insulin, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
7
29
1
2
Order By: Relevance
“…In the study evaluated the role of diet during pregnancy and lactation in rats in the induction of metabolic abnormalities, especially an oxidant/antioxidant imbalance was found that level of total antioxidant capacity and levels of antioxidant component increased following days in lactation period. In addition, it strongly has suggested that maternal fat and energy intake condition during lactation can play an important role in the development of metabolic disorders observed in their offspring, and that maternal oxidative stress can be singled out as the factor involved 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the study evaluated the role of diet during pregnancy and lactation in rats in the induction of metabolic abnormalities, especially an oxidant/antioxidant imbalance was found that level of total antioxidant capacity and levels of antioxidant component increased following days in lactation period. In addition, it strongly has suggested that maternal fat and energy intake condition during lactation can play an important role in the development of metabolic disorders observed in their offspring, and that maternal oxidative stress can be singled out as the factor involved 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of vitamin E and Se supplementation in maintenance of health and fertility in dairy cows has been widely investigated, although results are conflicting and still remain inconclusive. In a recent study in rats, it was observed that an improvement in maternal oxidant/ antioxidant status during pregnancy and lactation could have beneficial effects on the progeny (Bouanane et al 2009). Comparatively, less research work has been done to explore the role of oxidative stress and effects of antioxidant supplementation during pregnancy and early post partem period in water buffaloes.…”
Section: Introductionmentioning
confidence: 96%
“…Keesey and Hirvonen [14] suggest that the lack of weight gain could be explained by hypothalamic mechanisms, which establishes a set point that body weight and fat mass are regulated through coordinated adjustment to both energy intake and expenditure. On the other hand, studies show female Wistar rats exposed to high-fat diet during pregnancy and lactation presented an increased maternal body weight at parturition and at the end of lactation, showing that the hypercaloric diet resulted in an increased energy intake confirmed by an increased body fat and prevented body weight loss in lactating rats [15].…”
Section: Discussionmentioning
confidence: 99%